2000
DOI: 10.1093/jnci/92.11.924
|View full text |Cite
|
Sign up to set email alerts
|

Altered PTEN Expression as a Diagnostic Marker for the Earliest Endometrial Precancers

Abstract: Loss of PTEN function by mutational or other mechanisms is an early event in endometrial tumorigenesis that may occur in response to known endocrine risk factors and offers an informative immunohistochemical biomarker for premalignant disease. Individual PTEN-negative glands in estrogen-exposed endometria are the earliest recognizable stage of endometrial carcinogenesis. Proliferation into dense clusters that form discrete premalignant lesions follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

36
541
2
21

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(600 citation statements)
references
References 22 publications
36
541
2
21
Order By: Relevance
“…Type I, or endometrioid carcinomas, represents the majority of cases and may be found in premenopausal women exposed to excess levels of estrogen. The most common molecular alterations found in this subtype include PTEN inactivation [2], and mutations of K-ras [3], beta-catenin [4], or hMLH1/MSH2 [5]. These tumors frequently develop in a background of adenomatous hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Type I, or endometrioid carcinomas, represents the majority of cases and may be found in premenopausal women exposed to excess levels of estrogen. The most common molecular alterations found in this subtype include PTEN inactivation [2], and mutations of K-ras [3], beta-catenin [4], or hMLH1/MSH2 [5]. These tumors frequently develop in a background of adenomatous hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Although constitutive activation of Akt and/or PI3K is described in a growing list of solid tumors as a mechanism for transformation, [11][12][13][14][15] the most frequently mutated component of this pathway, by far, is PTEN, found to have an average mutation rate of 16% across many tumor types, to as high as 83% in endometrial cancers. 16 We have previously demonstrated that the PTEN protein is lost/reduced in 38% of human invasive breast cancers. 17 Our understanding of the signaling events that occur downstream of PTEN derives primarily from experimental models.…”
mentioning
confidence: 98%
“…Type I tumors exhibit endometrioid morphology, arise in the setting of increased estrogen exposure with subsequent development of precancerous lesions (endometrial intraepithelial hyperplasia-EIN/atypical hyperplasia), are associated with frequent PTEN inactivation mutations, and have a favorable outcome. 1,2 By contrast, Type II tumors demonstrate papillary serous or clear cell morphology, are not associated with any known precursor lesions, demonstrate frequent p53 mutations, and are associated with a poor outcome. 3,4 The differences between these groups are summarized in Table 1.…”
mentioning
confidence: 99%